2018
DOI: 10.1097/bot.0000000000001103
|View full text |Cite
|
Sign up to set email alerts
|

Physical Performance Limitations After Severe Lower Extremity Trauma in Military Service Members

Abstract: Objectives: To characterize the type and magnitude of lower extremity physical performance deficits in military service members who have undergone rehabilitation after limb salvage or transtibial amputation. Design: Cross-sectional prospective. Setting: Level I trauma military medical and rehabilitation center. Patients/Participants: Service members with lower ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
1
13
1
Order By: Relevance
“…Our findings suggest PDAFO users who complete MDT rehabilitation are able to demonstrate comparable functional and pain responses to elective BKA with advanced prosthesis provision (Figure 3 and Table 3). This observation has recently been demonstrated by US military rehabilitation centres 21…”
Section: Discussionsupporting
confidence: 53%
“…Our findings suggest PDAFO users who complete MDT rehabilitation are able to demonstrate comparable functional and pain responses to elective BKA with advanced prosthesis provision (Figure 3 and Table 3). This observation has recently been demonstrated by US military rehabilitation centres 21…”
Section: Discussionsupporting
confidence: 53%
“…Had the participant conducted the trials without her prosthetic leg, however, we would expect that she would have rated the usability of the adapted board more highly. As noted in one study, individuals with unilateral transtibial amputation who used a custom-fit prosthetic leg were able to perform similarly to individuals without amputation on a variety of physical performance measures [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that patients who underwent amputation had shorter time until full weight bearing (Saddawi-Konefka, Kim, and Chung, 2008), could walk greater distances, were more likely to be able to run (Ladlow et al, 2016), and had fewer gait deficiencies with more time spent on the affected limb (Mangan et al, 2016) compared with those who underwent reconstructive surgery. However, another study that examined longer-term mobility (an average of two years following surgery)-as measured by sit-to-stand, four-square step, and timed stair-ascent tests-found no difference between patients who underwent amputation and those who underwent limb salvage (Wilken et al, 2018).…”
Section: Functional Status After Surgerymentioning
confidence: 99%
“…All of the studies we identified focused on lower-limb amputation versus salvage, and most studies examined multiple or unspecified levels or degrees of amputation and salvage. The most-common specified levels of amputation and reconstruction were transtibial (Penn-Barwell et al, 2015;Saddawi-Konefka, Kim, and Chung, 2008;Wilken et al, 2018) and foot (Bennett et al, 2018;Sheean, Krueger, and Hsu, 2014). Those who underwent transtibial amputation were significantly more likely to return to active duty than those who underwent all other amputation levels .…”
Section: Surgical Level and Subsequent Outcomementioning
confidence: 99%